Prophage Gene Rv2650c Enhances Intracellular Survival of Mycobacterium smegmatis - Fan, Xiangyu; Liu, Zichen; Wan, Zhibin; Zou, Hanlu; Ji, Mengzhi; Sun, Kaili; Gao, Rongfeng; Li, Zhongfang; Li, Wu (Frontiers in Microbiology, 2022)
Background Induced by the pathogen Mycobacterium tuberculosis, tuberculosis remains one of the most dangerous infectious diseases in the world. As a special virus, prophage is domesticated by its host and are major contributors to virulence factors for bacterial pathogenicity. The function of prophages and their genes in M. tuberculosis is still unknown. Methods Rv2650c is a prophage gene in M. tuberculosis genome. We constructed recombinant Mycobacterium smegmatis (M. smegmatis) to observe bacteria morphology and analyze the resistance to various adverse environments. Recombinant and control strains were used to infect macrophages, respectively. Furthermore, we performed ELISA experiments of infected macrophages. Results Rv2650c affected the spread of colonies of M. smegmatis and enhanced the resistance of M. smegmatis to macrophages and various stress agents such as acid, oxidative stress, and surfactant. ELISA experiments revealed that the Rv2650c can inhibit the expression of inflammatory factors TNF-α, IL-10, IL-1β, and IL-6. Conclusion This study demonstrates that the prophage gene Rv2650c can inhibit the spread of colonies and the expression of inflammatory factors and promote intracellular survival of M. smegmatis. These results build the foundation for the discovery of virulence factors of M. tuberculosis, and provide novel insights into the function of the prophage in Mycobacterium.